Genome-wide analysis clarifies the population genetic structure of wild gilthead sea bream (Sparus aurata). - Francesco Maroso; Konstantinos Gkagkavouzis; Sabina De Innocentiis; Jasmien Hillen; Fernanda do Prado; Nikoleta Karaiskou; John Bernard Taggart; Adrian Carr; Einar Nielsen; Alexandros Triantafyllidis; Luca Bargelloni; Aquatrace Consortium (PLoS ONE)
Gilthead sea bream is an important target for both recreational and commercial fishing in Europe, where it is also one of the most important cultured fish. Its distribution ranges from the Mediterranean to the African and European coasts of the North-East Atlantic. Until now, the population genetic structure of this species in the wild has largely been studied using microsatellite DNA markers, with minimal genetic differentiation being detected. In this geographically widespread study, 958 wild gilthead sea bream from 23 locations within the Mediterranean Sea and Atlantic Ocean were genotyped at 1159 genome-wide SNP markers by RAD sequencing. Outlier analyses identified 18 loci potentially under selection. Neutral marker analyses identified weak subdivision into three genetic clusters: Atlantic, West, and East Mediterranean. The latter group could be further subdivided into an Ionian/Adriatic and an Aegean group using the outlier markers alone. Seascape analysis suggested that this differentiation was mainly due to difference in salinity, this being also supported by preliminary genomic functional analysis. These results are of fundamental importance for the development of proper management of this species in the wild and are a first step toward the study of the potential genetic impact of the sea bream aquaculture industry.